Synthetic Developments on the Indolizidine Alkaloid, Harmicine - Chakraborty, Indrajit; Jana, Samaresh (Synthesis, 2013)
Indolizidine alkaloids are widespread in Nature and display a wide spectrum of biological activity. Harmicine, as an example of an indolizidine alkaloid, shows antileishmanial and antinociceptive activity, and is an interesting target for synthetic organic chemists. This article provides a comprehensive review of the synthetic routes toward harmicine since its isolation in 1997.1 Introduction2 Synthetic Approaches3 Conclusions
Keywords: harmicine; β-carboline; indolizidines; alkaloids; antileishmania; antinociceptive; natural products